Validity and reproducibility of the revised oral assessment guide applied by community health workers. (7th January 2013) - Ribeiro, Marco Tulio F.; Ferreira, Raquel C.; Vargas, Andrea M.D.; e Ferreira, Efigênia Ferreira
<x xml:space="preserve">Abstract</x> Objective To determine the validity and reproducibility of the Revised Oral Assessment Guide (ROAG) as pre‐diagnostic tool used in elderly citizens by community health workers (CHWs) of the Family Health Strategy (FHS). Material and methods Initially, we adjusted the English version to Portuguese and then developed a training program for use of ROAG, with the participation of CHWs, in selected districts that had the highest enrolled number of elderly people in the city. The elderly persons were distributed among 10 previously trained CHWs. To assess the validity of the ROAG, a CHW and a dentist (considered as the gold standard) independently evaluated the same individual. The reproducibility of the ROAG was evaluated by each of the CHWs examining 5–6 elderly individuals twice with a 7‐day interval. Results The sensitivity ranged from 0.17 for evaluation of saliva to 0.80 for voice. The specific ranged from 0.69 for teeth/dentures to 0.98 for saliva using mirror and the accuracy ranged from 0.92 for swallow to 0.64 for mucosa. The intra‐rater reproducibility of the ROAG was perfect for evaluation of voice, lips and swallow (κ = 1.000). Conclusion When used by trained CHWs, the ROAG is a tool with high sensitivity and specificity to assess voice, swallowing, tongue and teeth/dentures. Moreover, it can efficiently detect patients showing no alteration in lips, saliva, mucosa and gums. High reproducibility was observed in almost all the categories. Trained CHWs can use this tool to improve the access of elderly patients to dental services.